Pengembangan Media Pembelajaran Komik Matematika Digital Pada Materi Bangun Ruang Siswa Kelas V SD - Dwinda Rusdiana; Treny Hera; Anggria Septiani Mulbasari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research is development research which aims to produce certain products. This research developed digital comic media which was carried out at MIN 10 Muara Enim which resulted in a product in the form of valid and practical digital comic media. This type of research is Research and Development. The development model used is the ADDIE model developed by Dick and Carey 1996, which has 5 stages, namely analysis, design, development, implementation and evaluation. The data collection technique used is through validation questionnaires, teacher practicality questionnaires and student response questionnaires, data analysis techniques use quantitative data analysis techniques, namely static descriptive. The results that the researchers got were that digital comic media was valid with a percentage for media of 92% and very valid with a percentage for material/language totaling 92.66%. Meanwhile, for practicality through student responses via the questionnaire, student responses were categorized as practical with an assessment percentage of 93.86%. The digital mathematics comic media in class V student building materials at MIN 10 Muara Enim is valid and practical so it can be used in mathematics learning.